2018
DOI: 10.1016/j.hpb.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Advanced imaging to predict response to chemotherapy in colorectal liver metastases – a systematic review

Abstract: Radiological data on the prediction of response to chemotherapy for CRLM is relatively sparse and heterogeneous. Despite that, a promising parameter might be ADC. Second, there seems to be a seemingly counterintuitive correlation between parameters that predict a good response and also predict poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 69 publications
(150 reference statements)
0
20
0
Order By: Relevance
“…The increase in the incidence of CRC among Chinese population in the past decade is closely related to the changes in people's living habits due to rapid economic development; these changes include unhealthy eating, drinking, smoking, lack of exercise and obesity (Zhu et al, 2017). Although the use of surgery and comprehensive treatment has benefited many CRC patients, nearly half of the patients who undergo radical surgery may relapse, and patients who die from CRC liver metastases account for more than 50% of all CRC-related deaths (Enomoto and Igaki, 2011;Beckers et al, 2018). The occurrence of CRC is an extremely complicated process that may involve biological behaviours such as cell proliferation, metabolism, apoptosis, invasion and metastasis Weinberg, 2000, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the incidence of CRC among Chinese population in the past decade is closely related to the changes in people's living habits due to rapid economic development; these changes include unhealthy eating, drinking, smoking, lack of exercise and obesity (Zhu et al, 2017). Although the use of surgery and comprehensive treatment has benefited many CRC patients, nearly half of the patients who undergo radical surgery may relapse, and patients who die from CRC liver metastases account for more than 50% of all CRC-related deaths (Enomoto and Igaki, 2011;Beckers et al, 2018). The occurrence of CRC is an extremely complicated process that may involve biological behaviours such as cell proliferation, metabolism, apoptosis, invasion and metastasis Weinberg, 2000, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The KRAS/NRAS/BRAF are the downstream effectors of the EGFR signal pathway involved in tumor cell proliferation, differentiation, and invasion ( 26 ). Tumors with mutant genes more likely exhibit greater aggressiveness and angiogenesis, which will result in faster progress, worse survival, and lower apparent diffusion coefficient (ADC) value ( 27 ). The DWI can indicate the functional information of tissue by evaluation of water molecular mobility, which is estimated with ADC value, while T2WI are prone to indicate anatomic information, which might explain the higher genotype prediction performance of DWI compared to that of T2WI.…”
Section: Discussionmentioning
confidence: 99%
“…significant correlation may be attributed to the routine use of MRI for therapeutic evaluations at our hospital. It has also been revealed that the apparent diffusion coefficient of MRI is the most precise parameter for predicting the chemotherapy response in CRLM patients (33). The occurrence of major postoperative complications in CRLM patients often leads to unfavorable outcomes, such as poor quality of life, extended recovery time, and increased economic and physical stress.…”
Section: Predictive Value Of the Pre-nac Rdw Level And The Preoperative Rdw Level On Pfs And Osmentioning
confidence: 99%